Blind source separation communication anti-jamming technology and practice - Fuqiang YAO; Miao YU; Pengcheng GUO; Miaomiao GU (Tongxin xuebao)
Aiming at the threat of broad frequency band suppressing jamming and the inherent contradiction between spectrum resources and communication anti-jamming ability, a method was proposed to add the statistics domain dimension on the basis of spread spectrum anti-jamming, which promoted the transformation of communication anti-jamming from hard anti-jamming to accommodate the jamming.The statistical characteristics difference between communication signal and jamming signal was utilized by blind source separation (BSS) communication anti-jamming technology to separate signals, which could improve the communication anti-jamming ability without increasing spectrum resources.To understand and improve the development process of BSS communication anti-jamming (BSSCA) from theory and algorithm to engineering practice, the basic principle of BSSCA was described, the key technologies such as multi-channel BSS and single channel BSS were emphasized.The main characteristics and existing problems of BSSCA were analyzed.Finally, the development priorities of this field were pointed out.